Seven samurai [videorecording (Blu-Ray)] - Motoki, Sōjirō; Kurosawa, Akira, 1910-1998; Hashimoto, Shinobu, 1918-2018; Oguni, Hideo, 1904-1996; Mifune, Toshiro, 1920-1997; Shimura, Takashi, 1905-1982; Tsushima, Keiko, 1926-2012; Shimazaki, Yukiko, 1931-; Fujiwara, Kamatari, 1905-1985; Katō, Daisuke, 1911-1975; Kimura, Isao, 1923-1981; Chiaki, Minoru, 1917-1999; et al. (Criterion Collection, 2010)
The story of a sixteenth century village whose desperate inhabitants hire the eponymous warriors to protect them from invading bandits.